Transitivity in Atukwei Okai’s “The Oath of Fontomfrom” - Owusu, Edward; Botchwey, Emmanuel; Afful , Joseph Benjamin Archibald; Yeboah, Asuamah Adade; Asinyor, Ebenezer; Gyasi, Abraham (International Journal of Language and Literary Studies, 2022)
Examining the language of a literary text can be a reliable way of comprehending literary writers’ experiences. This paper explores the relationship between linguistic forms and socially construed meaning in Atukwei Okai’s poem, “The Oath of the Fontomfrom”. The objectives of the study were to (1) examine the poet’s process choices and their typical distribution in the text, (2) assess the participant characteristics of each process category, and (3) establish the role of the speaker/persona in the poem. This descriptive qualitative study was underpinned by the transitivity framework of Halliday and Matthiessen’s (2014) Systemic Functional Linguistics. So, a content analysis tool was used in analysing the text by revealing how meaning is presented. The results revealed that the poet (or persona) used different kinds of processes to present meaning to his reader.Consequently, when these processes were analysed, the results indicated that material processes were most frequently used. The distribution of process types includes 42% material, 16% mental, 15% behavioural, 13% relational, and 10% verbal processes. Again, the persona is involved in 32 processes, constituting 35% of the total processes. The preponderance of material processes revealed that the poet portrayed warfare as mainly involving concrete physical actions.